POLISH LITERATURE OF THE LATE 19TH AND EARLY 20TH CENTURIES IN IVAN FRANKO’S CRITICAL RECEPTION - Golod, Roman (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
The article is dedicated to the study of Franco’s literary-critical reception of the works of Polish writers of the late 19th - early 20th centuries. The focus is on Polish literary positivism, naturalism, realism, and modernism. The level of scientific development of the theme "Franco and Polish literature" in domestic and foreign literary criticism is described. The methods of researching the declared topic are indicated. Literary research of Ivan Franko, devoted to the creativity of Bolesław Prus, Maria Konopnicka, Jan Kasprowicz, Bogdan Zaleski, Teofil Lenartowicz, Adam Asnyk, Stanislaw Przybyszewski are analyzed. The boundaries of the influence of romantic traditions in general and the creativity of Adam Mickiewicz in particular on Polish literature of later generations are clarified. The evolution of Ivan Franko’s literary-critical views on the creativity of Adam Mickiewicz is taken into account. The attitude of I. Franko to the dialectics of traditions and innovation in Polish and Ukrainian literary processes of the late 19th - early 20th centuries is analyzed. The significance of positivism in the intellectual, cultural and literary life of Poland and Ukraine is studied. Attention is paid to the determinants of Franco’s interest in the philosophical doctrine of positivism. A comparative analysis of naturalistic and realistic tendencies in the works of I. Franco, E. Zola, and Polish writers of the late 19th century is carried out. The contribution of Ivan Franko to the popularization of positivism and naturalism in Poland and to acquainting Ukrainian readers with the creativity of Polish writers is described. The peculiarities of Franco’s critical perception of modern trends in Ukrainian and Polish literary processes are revealed. The features of Franco’s critical perception of tendencies towards the absolutization of the doctrine of utilitarian perception of literature and the concept of "art for art’s sake" are clarified. The integration of Ivan Franko into the Polish cultural-historical and literary process and the significance of his literary-critical heritage for the establishment of Ukrainian-Polish intercultural relations is proven.